Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Motivasi Kerja sebagai Variabel Intervening pada Cv. Timbul Jaya Motor Kediri - Selvina Adismaya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to determine the direct and indirect influence of leadership style and work environment on employee performance through work motivation as an intervening variable. This type of research uses quantitative because it leads to measurement methods and samples to test variables and hypotheses. The data sources in this research use primary and secondary data. The sample in the research was 31 CV employees. Timbul Jaya Motor Kediri uses a saturated sampling technique which uses all members of the population as samples. The analysis technique used is the measurement model test or outer model including the discriminant validity test, average and the structural model test or inner model which includes the R-square, Q-square test and hypothesis test.. The results of the research show that Leadership Style (X1), and Work Environment (X2), Work Motivation (Z) have a significant and positive effect directly on Employee Performance (Y) and Leadership Style (X1), and Work Environment (X2) indirectly has a significant and positive effect on Employee Performance (Y) through Work Motivation (Z) as an intervening variable. This research also shows that the coefficient of determination (R2) of employee performance variables has an influence of 88.9% in influencing leadership style and work environment variables while the remaining 11.1% is influenced by other variables not discussed in this research so that further research uses other variables outside this research. In this study, it is implemented that a company's performance factors are influenced and can be improved through leadership style and work environment variables through work motivation.